Ibandronate to treat skeletal-related events and bone pain in metastatic bone disease or multiple myeloma: a meta-analysis of randomised clinical trials. Issue 6 (2nd June 2015) - Geng, Chun-Jing; Liang, Qian; Zhong, Jian-Hong; Zhu, Min; Meng, Fan-Ying; Wu, Ning; Liang, Rui; Yuan, Bin-Yi
Abstract : Objective: Randomised controlled trials (RCTs) have given contradictory results about the efficacy and safety of ibandronate in treating metastatic bone disease (MBD) or multiple myeloma. This review meta-analysed the literature to gain a more comprehensive picture. Design: Systematic review and meta-analysis of ibandronate compared with placebo or zoledronate. Data sources: PubMed, EMBASE and the Cochrane Library databases were systematically searched to identify RCTs published up to March 2015 evaluating ibandronate to treat MBD or multiple myeloma. Review method: 10 RCTs involving 3474 patients were included. Six RCTs were placebo-controlled and four compared ibandronate with zoledronate. The studies included in this review were mainly from European countries. Results: Intravenous ibandronate (6 mg) or oral drug (50 mg) decreased the risk of skeletal-related events compared to placebo (risk ratio (RR) 0.80, 95% CI 0.71 to 0.90, p=0.002). It also reduced the bone pain score below baseline significantly more than did placebo at 96 weeks (weighted mean difference −0.41, 95% CI −0.56 to −0.27, p<0.001). The incidence of diarrhoea, nausea and adverse renal events was similar between the ibandronate and placebo groups, but ibandronate was associated with greater risk of abdominal pain. Ibandronate was associated with similar risk of skeletal-related events as another bisphosphonate drug, zoledronate (RR 1.02, 95% CI 0.82 to 1.26, p=0.87). The incidence of nausea, jaw osteonecrosis and fatigue was similar for the two drugs, but the incidence of adverse renal events was significantly lower in the ibandronate group. Conclusions: Ibandronate significantly reduces the incidence of skeletal-related events and bone pain in patients with MBD or multiple myeloma relative to placebo. It is associated with a similar incidence of skeletal-related events as zoledronate.